ENHANCING SKILLS ON BILL OF QUANTITY PREPARATION FOR STUDENTS OF BUILDING ENGINEERING EDUCATION STUDY PROGRAM AT UNIVERSITY OF PALANGKA RAYA - Wiyogo; Patrisia, Yulin (Jurusan Pendidikan Teknologi dan Kejuruan, FKIP, Universitas Palangkaraya, 2019)
This community service aimed to equip participants with the skills needed in entrepreneurial ability. By transferring the knowledge for students in the Building Engineering Education Study Program, it was expected that the participants will be more skilled in carrying out planning, supervision, and construction implementation. The module provided the skill on preparation of the bill of quantity for building construction. The community service was held in the Building Engineering Education Study Program FKIP UPR from August 2019 to November 2019. The training methods used were lectures with presentation techniques, guided hands-on practice and evaluation. The output were an increase in participant skills, training module, final report and publication in scientific journals. Activities run smoothly, participants were present according to the target. The participants were able to (1) knowing the initial concept of forming and compiling bill of quantity. (2) analyzing the quantity; (3) calculating the number of labor and material needs based on Permenkeu and Indonesian Standard, (4) Participants are able to use Microsoft Excel as a tool in making the bill of quantity.